Gate-Level Hardware Countermeasure Comparison against Power Analysis Attacks - Erica Tena-Sánchez; Francisco Eugenio Potestad-Ordóñez; Carlos J. Jiménez-Fernández; Antonio J. Acosta; Ricardo Chaves (Applied Sciences, 2022)
The fast settlement of privacy and secure operations in the Internet of Things (IoT) is appealing in the selection of mechanisms to achieve a higher level of security at minimum cost and with reasonable performances. All these aspects have been widely considered by the scientific community, but more effort is needed to allow the crypto-designer the selection of the best style for a specific application. In recent years, dozens of proposals have been presented to design circuits resistant to power analysis attacks. In this paper, a deep review of the state of the art of gate-level countermeasures against power analysis attacks has been carried out, performing a comparison between hiding approaches (the power consumption is intended to be the same for all the data processed) and the ones considering a masking procedure (the data are masked and behave as random). The most relevant proposals in the literature, 35 for hiding and 6 for masking, have been analyzed, not only by using data provided by proposers, but also those included in other references for comparison. Advantages and drawbacks of the proposals are analyzed, showing quantified data for cost, performance (delay and power), and security when available. One of the main conclusions is that the RSL proposal is the best in masking, while TSPL, HDRL, SDMLp, 3sDDL, TDPL, and SABL are those with the best security performance figures. Nevertheless, a wise combination of hiding and masking as masked_SABL presents promising results.